Leveraging edge artificial intelligence for sustainable agriculture - El Jarroudi, M.; Kouadio, L.; Delfosse, P.; Bock, C. H.; Mahlein, A. K.; Fettweis, X.; Mercatoris, B.; Adams, F.; Lenné, J. M.; Hamdioui, S. (2024)
Effectively feeding a burgeoning world population is one of the main goals of sustainable agricultural practices. Digital technology, such as edge artificial intelligence (AI), has the potential to introduce substantial benefits to agriculture by enhancing farming practices that can improve agricultural production efficiency, yield, quality and safety. However, the adoption of edge AI faces several challenges, including the need for innovative and efficient edge AI solutions and greater investment in infrastructure and training, all compounded by various environmental, social and economic constraints. Here we provide a roadmap for leveraging edge AI at the intersection of food production and sustainability.